2018
DOI: 10.1039/c8cp91812k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Improved fill factor in inverted planar perovskite solar cells with zirconium acetate as the hole-and-ion-blocking layer

Abstract: Correction for ‘Improved fill factor in inverted planar perovskite solar cells with zirconium acetate as the hole-and-ion-blocking layer’ by Xuewen Zhang et al., Phys. Chem. Chem. Phys., 2018, 20, 7395–7400.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results of the J – V characteristics of the devices in forward and reverse scanning also showed that the hysteresis of the Zr-SnO 2 device was obviously weakened after incorporation of ZrAcac (Figure S17). The hysteresis is closely related to the accumulation of ionic charge at the interface. , The mitigated hysteresis is consistent with the reduced interface charge density of the Zr-SnO 2 device.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The results of the J – V characteristics of the devices in forward and reverse scanning also showed that the hysteresis of the Zr-SnO 2 device was obviously weakened after incorporation of ZrAcac (Figure S17). The hysteresis is closely related to the accumulation of ionic charge at the interface. , The mitigated hysteresis is consistent with the reduced interface charge density of the Zr-SnO 2 device.…”
Section: Resultssupporting
confidence: 53%
“…Zirconium acetylacetonate (ZrAcac) has been successfully used as a buffer layer between the active layer and the cathode or between the ETL and the cathode, resulting in enhanced electron extraction. However, ZrAcac was mainly used in PSCs with a p-i-n structure, and it is rarely used in a n-i-p PSC with SnO 2 as the ETL.…”
Section: Introductionmentioning
confidence: 99%